2018
DOI: 10.1111/jvim.15084
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two melphalan protocols and evaluation of outcome and prognostic factors in multiple myeloma in dogs

Abstract: BackgroundMultiple myeloma (MM) in dogs typically is treated with melphalan. A daily melphalan dosing schedule reportedly is well tolerated and associated with favorable outcome. Although anecdotally a pulse dose regimen has resulted in successful responses, little long‐term outcome and safety data is available regarding this dosing regimen for dogs with MM.Hypothesis/objectives(1) To compare outcome and adverse event profiles between pulse dose and daily dose melphalan schedules and (2) to report prognostic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 55 publications
(107 reference statements)
2
63
3
1
Order By: Relevance
“…Quantification of immunoglobulins in the dog has largely been restricted to the use of the radial immunodiffusion (RID), ELISA, and automated immunoturbidometric methods; based on current literature, RID appears to be the most commonly used method in veterinary medicine for quantifying the total amount of immunoglobulin . Anecdotally, we observed that the IgA RID kit significantly overestimated immunoglobulin concentrations and had poor diagnostic utility, similar to what has been documented in human medicine .…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Quantification of immunoglobulins in the dog has largely been restricted to the use of the radial immunodiffusion (RID), ELISA, and automated immunoturbidometric methods; based on current literature, RID appears to be the most commonly used method in veterinary medicine for quantifying the total amount of immunoglobulin . Anecdotally, we observed that the IgA RID kit significantly overestimated immunoglobulin concentrations and had poor diagnostic utility, similar to what has been documented in human medicine .…”
Section: Introductionsupporting
confidence: 56%
“…A panel of IgG, IgA, and IgM RID tests have been used to determine immunotypes . However, due to the performance characteristics of the RID tests, this practice proved to be unreliable in these samples.…”
Section: Discussionmentioning
confidence: 99%
“…Increased NLR is an indicator of systemic inflammation and is associated with increased circulating cytokines . Neutrophil‐to‐lymphocyte ratio has been used as a prognostic factor in both humans and dogs with malignancies . Evaluating NLR can compensate for fluctuations between individual neutrophil and lymphocyte counts.…”
Section: Discussionmentioning
confidence: 99%
“…6,17 In human medicine, plasma cell leukemia is the most aggressive presentation of the plasma cell neoplasms and is characterized by circulating plasma cells > 2 × 10 9 /L or 20% of the 19 Primary plasma cell leukemia is a malignant proliferation of plasma cells first diagnosed in the leukemic phase; secondary plasma cell leukemia corresponds to the leukemic transformation of primary underlying multiple myeloma. 9,19 In our case, using human and canine criteria for the differential diagnosis, many features were more consistent with primary plasma cell leukemia than leukemic multiple myeloma. The high tumor burden and >20% circulating neoplastic cells at the time of the dog's initial presentation is more consistent with primary plasma cell leukemia than with leukemic multiple myeloma.…”
mentioning
confidence: 54%